Double-layer antireflection film, double-layer antireflection film glass as well as preparation method and application of double-layer antireflection film glass
By adopting a double-layer urgency film structure on solar photovoltaic glass, and using materials such as TiO2 and SiO2 to improve light transmittance and weather resistance, the problem of light transmittance decline caused by interface reflection and environmental factors of photovoltaic glass is solved, and more efficient light energy conversion is achieved.
Patent Information
- Application Number
- CN202411879120.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-25
AI Technical Summary
During the use of existing solar photovoltaic glass, the light transmittance decreases due to interface reflection and environmental factors, affecting the light energy conversion efficiency.
A double-layer resistant film structure is adopted, wherein the first film layer contains 25-65% TiO2 and 25-65% SiO2, and the second film layer contains 75-94% TiO2, 0.5-8% GQDs and 5-15% other components. The light transmittance and weather resistance of the film layer are improved through this combination.
It has achieved the improvement of the overall light transmittance and weather resistance of solar photovoltaic glass, enhanced its resistance to diversified environmental factors, and reduced the photo loss of photovoltaic glass.
Smart Images

Figure BDA0005197730920000161
Abstract
Description
Technical Field
[0001] The invention belongs to the field of anti-reflection films, and in particular relates to a double-layer anti-reflection film, a double-layer anti-reflection film glass, and a preparation method and application thereof. Background Art
[0002] Solar photovoltaic glass is a special glass that uses solar radiation to generate electricity by laminating into solar cells. However, during the use of solar photovoltaic glass, the interface between it and the air will reflect about 6% of the sunlight, making this part of the sunlight unable to participate in the photoelectric conversion process, resulting in a certain amount of light loss. Furthermore, solar photovoltaic glass is mainly installed outdoors. Therefore, after long-term use, dust in the air can easily wash the glass surface due to air flow and rain, which will cause the transmittance of the photovoltaic glass to decrease, seriously affecting the efficiency of light energy conversion.
[0003] In order to improve the light conversion efficiency of solar photovoltaic glass, the mainstream method is to coat the surface of photovoltaic glass with a film containing SiO2 polymer. Some literature also adds pore-forming agents during the preparation of the film to enhance the light transmittance of the film, forming a porous silica anti-reflection film. Although the film prepared by this technology has good light transmittance, it has weak resistance to various environmental factors. Under the influence of environmental factors, the light transmittance of the film continues to decrease. Summary of the invention
[0004] The main purpose of the present invention is to provide a double-layer anti-reflection film, a double-layer anti-reflection film glass and a preparation method and application thereof. The technical problem to be solved is how to provide a double-layer anti-reflection film so that the overall light transmittance of the film layer is good and can resist various environmental erosions.
[0005] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. A double-layer antireflection film proposed in the present invention comprises:
[0006] The first film layer comprises, by mass percentage, 25-65% TiO2, 25-65% SiO2, and 5-15% other components;
[0007] The second film layer is arranged on the first film layer, and comprises, by weight percentage, 75-94% TiO2, 0.5-8% GQDs, and 5-15% other components.
[0008] The purpose of the present invention and the technical problem to be solved are also achieved by adopting the following technical solutions. A double-layer anti-reflection film glass proposed in the present invention comprises:
[0009] Glass substrate;
[0010] The first film layer is disposed on a single side of the glass substrate and comprises, by weight percentage, 25-65% TiO2, 25-65% SiO2, and 5-15% other components;
[0011] The second film layer is arranged on a single side of the first film layer away from the glass substrate, and comprises, by weight percentage, 75-94% TiO2, 0.5-8% GQDs, and 5-15% other components.
[0012] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.
[0013] Preferably, in the aforementioned double-layer anti-reflection film glass, the thickness of the first film layer and the second film layer are both 6-8 μm.
[0014] The purpose of the present invention and the technical problem solved by the present invention are also achieved by adopting the following technical solutions. According to a method for preparing a double-layer anti-reflection film glass proposed by the present invention, the method comprises the following steps:
[0015] The glass substrate was sequentially washed with water and pre-treated by rinsing with ethanol;
[0016] The first film layer precursor is coated on one side of the glass substrate, and then dried at a temperature of 150 to 200° C. for 1 to 2 hours to form a first film layer;
[0017] The first film layer is wiped with anhydrous ethanol, and after the surface is dried, a second film layer precursor is coated on the first film layer, and then dried at a temperature of 150-200° C. for 1-2 hours to form the second film layer.
[0018] Preferably, in the above scheme, TiO2 sol, SiO2 sol and organic solvent are mixed to form a first mixed solution, wherein the first mixed solution comprises 11-14% TiO2 sol and 7-9% SiO2 sol by mass percentage; the first mixed solution is subjected to ultrasonic and stirring treatment to be mixed uniformly, sealed and aged, and the formed TiO2 / SiO2 composite sol is the film-forming precursor of the first film layer shown;
[0019] TiO2 sol, GQDs and deionized water are mixed to form a second mixed solution, wherein the second mixed solution includes 57-62% TiO2 sol and 0.2-1% GQDs by mass percentage; the second mixed solution is subjected to ultrasonic and stirring treatment to be mixed uniformly, and sealed and aged to form a TiO2 / GQDs composite sol, which is the film-forming precursor of the second film layer;
[0020] The mass percentage of TiO2 in the TiO2 sol is 20-30%; the mass percentage of SiO2 in the SiO2 sol is 30-50%.
[0021] Preferably, in the aforementioned preparation method, the preparation of the GQDs comprises the following steps:
[0022] The graphene is oxidized by using a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid to obtain graphene oxide;
[0023] Graphene oxide, sodium carbonate, m-phenylenediamine and anhydrous ethanol are uniformly mixed by ultrasonication in a mass ratio of 1:1-3:3-5:90-110, and reacted at a temperature of 180-220°C for 4-8h; after the reaction is completed, the solid is filtered out and the solid is decontaminated to obtain GQDs.
[0024] Preferably, in the aforementioned preparation method, the preparation of the TiO2 sol comprises the following steps:
[0025] Under stirring conditions, dilute acid solution is added to each liter of a mixture of tetrabutyl titanate and anhydrous ethanol at a rate of 10 to 20 mL / min, the pH of the mixture of tetrabutyl titanate and anhydrous ethanol is adjusted to 2 to 3, the mixture is reacted for 20 to 40 minutes, and then the reaction solution is aged, impurities are removed, and dried to form a TiO2 sol, wherein the mass percentage of tetrabutyl titanate in the mixture of tetrabutyl titanate and anhydrous ethanol is 30 to 50%.
[0026] Preferably, in the aforementioned preparation method, the preparation of the SiO2 sol comprises the following steps:
[0027] Under stirring conditions, dilute acid solution is added to each liter of a mixture of tetraethyl orthosilicate and anhydrous ethanol at a rate of 10 to 20 mL / min, the pH value of the mixture of tetraethyl orthosilicate and anhydrous ethanol is adjusted to 2 to 3, the mixture is reacted for 20 to 40 minutes, and then the reaction solution is aged, impurities are removed, and dried to form a SiO2 sol; the mass percentage of tetraethyl orthosilicate in the mixture of tetraethyl orthosilicate and anhydrous ethanol is 40 to 60%.
[0028] The purpose of the present invention and the technical problems solved therein are also achieved by the following technical solutions: The double-layer anti-reflection film or double-layer anti-reflection film glass proposed in the above-mentioned solution of the present invention is applied in the fields of optical devices, display technology, photovoltaic industry, building materials, and transportation.
[0029] The purpose of the present invention and the technical problems solved by the present invention are also achieved by the following technical solutions: A solar photovoltaic glass proposed by the present invention comprises the double-layer anti-reflection film or double-layer anti-reflection film glass described in the above solution.
[0030] By means of the above technical solution, the double-layer anti-reflection film, double-layer anti-reflection film glass and the preparation method and application thereof proposed in the present invention have at least the following advantages:
[0031] 1. A double-layer anti-reflection film provided by the present invention improves the overall light transmittance of the double-layer anti-reflection film by designing TiO2 as one of the main components in the first film layer and the second film layer. In addition, SiO2 is added to the first film layer of the present invention, and a small amount of GQDs is added to the second film layer arranged on the first film layer, so that the weather resistance and dust and moisture-proof effects of the prepared film layer are enhanced, and the light transmittance is further improved.
[0032] 2. The double-layer anti-reflection film glass provided by the present invention has good light transmittance and strong weather resistance, can be applied to solar photovoltaic glass, and can resist the erosion of solar photovoltaic glass by various environmental factors.
[0033] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. DETAILED DESCRIPTION
[0034] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a double-layer anti-reflection film, double-layer anti-reflection film glass and its preparation method and application proposed by the present invention in combination with the preferred embodiments. Its specific implementation method, structure, characteristics and effects are described in detail as follows.
[0035] The present invention provides a double-layer anti-reflection film. In order to improve the overall light transmission effect of the double-layer anti-reflection film, TiO2 is designed as one of the main components in the first film layer and the second film layer, so that the optical properties between the double-layer films match each other, and the overall light transmittance of the double-layer anti-reflection film is improved. Further, SiO2 is added to the first film layer to improve the weather resistance of the film layer, and can reduce the light scattering effect, so that more light passes through the film layer into the substrate during the use of the double-layer anti-reflection film; further, a small amount of graphene quantum dots (GQDs) is added to the second film layer arranged on the first film layer, so that the weather resistance and dust and moisture resistance of the first film layer are enhanced, and the light transmission effect in the double-layer film layer is improved, and the reflection effect of light in the double-layer film layer is reduced, thereby increasing the light entering the interior of the substrate during the use of the double-layer anti-reflection film.
[0036] Preferably, in some embodiments, in order to make the double-layer anti-reflection film provided by the present invention have good weather resistance and good transmittance, the first film layer, calculated by mass percentage, includes: 25-65% TiO2, 25-65% SiO2, 5-15% other components; it includes: 75-94% TiO2; 0.5-8% GQDs; 5-15% other components.
[0037] Some embodiments of the present invention further provide a double-layer anti-reflection film glass, which includes:
[0038] Glass substrate: The glass substrate can be glass of any material.
[0039] The first film layer is disposed on a single side of the glass substrate and comprises, by weight percentage, 25-65% TiO2, 25-65% SiO2, and 5-15% other components;
[0040] The second film layer is disposed on a single side of the first film layer away from the glass substrate, and comprises, by mass percentage, 75-94% TiO2, 0.5-8% GQDs, and 5-15% other components, wherein the other components include solvents that have not been completely evaporated or impurities that have not been removed.
[0041] The present invention provides a double-layer anti-reflection film glass, in which TiO2 is one of the main components of the first film layer and the second film layer of the anti-reflection film, so that the optical properties of the double-layer films match each other to improve the overall light transmission effect of the double-layer anti-reflection film; further, the present invention adds SiO2 to the first film layer that is in direct contact with the glass, so as to improve the weather resistance of the film layer, and can reduce the light scattering effect, thereby helping more light to enter the glass through the film layer; further, the present invention adds a small amount of GQDs to the second film layer arranged on the first film layer, which is in contact with the external environment, thereby enhancing the overall weather resistance of the double-layer film layer, and enhancing the dust and moisture resistance of the film layer, and can improve the light conduction effect in the double-layer film layer, reduce the light reflection effect in the double-layer film layer, thereby increasing the light entering the interior of the glass through the double-layer anti-reflection film provided by the present invention.
[0042] Furthermore, in order to improve the resistance of the film layer to various environments and the overall light transmittance of the double-layer anti-reflection film glass, in some embodiments, the thickness of the first film layer and the second film layer are preferably 6-8 μm.
[0043] In some embodiments of the present invention, a method for preparing a double-layer anti-reflection film glass is also provided, which comprises the following steps:
[0044] 1) Glass pretreatment
[0045] Rinse the glass to be coated with distilled water or purified water several times to clean the glass surface, then rinse with ethanol and dry the glass surface to ensure the cleanliness of the glass surface.
[0046] 2) Preparation of the first film layer: The first film layer precursor, i.e., TiO2 / SiO2 composite sol, is uniformly coated on the glass surface; after coating, the glass containing the first film layer precursor is placed at a temperature of 150-200°C and baked and dried for 1-2 hours to solidify the film layer, and then cooled and taken out, and the preparation of the first film layer is completed.
[0047] 3) Preparation of the second film layer: The glass that has completed the preparation of the first film layer is wiped with ethanol on the surface of the first film layer to remove dust and impurities, and the surface is dried. In some embodiments, the water content of the ethanol is preferably ≤30%. It is further preferred that the ethanol is wiped 2 to 5 times to reduce the impact of ethanol on the first film layer while keeping the film layer clean. After the first film layer is cleaned, the second film layer precursor, i.e., the TiO2-GQDs composite sol, is evenly coated on the surface of the first film layer; after the coating is completed, the glass is placed at a temperature of 150 to 200°C and baked and dried for 1 to 2 hours to solidify the film layer, cooled and taken out, and the preparation of the second film layer is completed.
[0048] In some embodiments, the preparation of the first film layer film precursor comprises the following steps:
[0049] TiO2 sol, SiO2 sol and organic solvent are mixed to form a first mixed solution, wherein the first mixed solution includes 11-14% TiO2 sol and 7-9% SiO2 sol by mass percentage. The first mixed solution is ultrasonicated at room temperature (ultrasonic frequency is 20-40KHz), and stirred at a speed of 20000-25000r / h for 8-12h to mix evenly, and then sealed and aged for 12-24h at room temperature. The formed TiO2 / SiO2 composite sol is the first film layer precursor. In some embodiments, the organic solvent dispersant is any one of methanol and ethanol or a mixture thereof; preferably, the organic solvent dispersant is ethanol.
[0050] In some embodiments, the preparation of the second film layer film precursor comprises the following steps:
[0051] TiO2 sol, GQDs and deionized water are mixed to form a second mixed solution, wherein the second mixed solution comprises, by mass percentage, 57-62% TiO2 sol and 0.2-1% GQDs. The second mixed solution is ultrasonicated at room temperature (ultrasonic frequency is 20-40KHz), and stirred at a speed of 20000-25000r / h for 6-10h to mix evenly, and then sealed and aged for 12-24h at room temperature, and the formed TiO2 / GQDs composite sol is the second film layer film precursor.
[0052] In the above scheme, the mass percentage of TiO2 in the TiO2 sol is 20-30%; the mass percentage of SiO2 in the SiO2 sol is 30-50%.
[0053] In some embodiments of the present invention, a method for preparing the GQDs is further provided, comprising the following steps:
[0054] First, the graphene is immersed in a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid for oxidation treatment, wherein the mass ratio of concentrated sulfuric acid to concentrated nitric acid in the mixed acid solution is 3-5:1, and the graphene is filtered out after immersion for 0.5-1h to obtain graphene oxide.
[0055] Then, graphene oxide, sodium carbonate, m-phenylenediamine and anhydrous ethanol are mixed in a mass ratio of 1:1-3:3-5:90-110. Preferably, the oxidized graphene, sodium carbonate, m-phenylenediamine and anhydrous ethanol are mixed in a mass ratio of 1:1.5-2.5:1.5-4.6:95-105. More preferably, the oxidized graphene, sodium carbonate, m-phenylenediamine and anhydrous ethanol are mixed in a mass ratio of 1:2:4:100. The above mixture is further placed in a corrosion-resistant container and sealed, and ultrasonically mixed evenly, and the ultrasonic frequency and time are not limited. After the graphene, sodium carbonate, m-phenylenediamine and anhydrous ethanol are ultrasonically mixed evenly, they are reacted at a temperature of 180-220°C for 4-8 hours.
[0056] After the reaction is completed, the mixture is cooled, the solid is filtered out, and the solid is purified to remove impurities. In some embodiments, a semipermeable membrane is used to remove impurities to obtain the GQDs.
[0057] In some embodiments, a method for preparing the TiO2 sol is also provided, which comprises the following steps:
[0058] Preparation of mixed solution A: Tetrabutyl titanate and anhydrous ethanol are uniformly mixed to form mixed solution A, wherein the mass percentage of tetrabutyl titanate in the mixed solution A is 30-50%.
[0059] Dilute acid solution: The content of hydrogen ions in the dilute acid solution is 0.01-0.001 mol / L; in some embodiments, the dilute acid solution is a mixture of any one or more of dilute hydrochloric acid, dilute sulfuric acid, and dilute nitric acid.
[0060] Under stirring (stirring speed is 300-1000rpm), dilute acid is slowly added to the mixed solution A at a speed of 10-20mL / min to form a mixed solution, the pH of the mixed solution A is adjusted to 2-3, and stirred for reaction for 20-40min to form a reaction solution, which is a TiO2 suspension. The addition speed of the dilute acid is strictly controlled to make the reaction proceed evenly. If the TiO2 suspension is formed by adding too quickly, it is easy to stratify. If the TiO2 suspension is formed by adding too slowly, the reaction is incomplete, and the TiO2 suspension formed has low content and poor stability.
[0061] After the reaction is completed, the TiO2 suspension is allowed to stand and age for 4 to 6 days. After aging, large particles are filtered out, and then the aged sol is washed with water to remove impurities, and dried at 80 to 120 degrees to remove moisture and volatile substances to obtain a stable TiO2 sol, in which the mass percentage of TiO2 is 20 to 30%.
[0062] In some embodiments, a method for preparing the SiO2 sol is also provided, which comprises the following steps:
[0063] Mixed solution E: Tetraethyl orthosilicate and anhydrous ethanol are mixed uniformly at room temperature to form a mixed solution E, wherein the mass percentage of tetraethyl orthosilicate in the mixed solution E is 40-60%.
[0064] Dilute acid solution: The content of hydrogen ions in the dilute acid solution is 0.01-0.001 mol / L; in some embodiments, the dilute acid solution is a mixture of any one or more of dilute hydrochloric acid, dilute sulfuric acid, and dilute nitric acid.
[0065] Under stirring (stirring speed is 300-1000rpm), dilute acid is slowly added to the mixed solution E at a speed of 10-20mL / min to form a mixed solution, the pH of the mixed solution E is adjusted to 2-3, and stirred for reaction for 20-40min to form a reaction solution, which is a SiO2 suspension. The addition speed of the dilute acid is strictly controlled to make the reaction proceed uniformly. If the SiO2 suspension is added too quickly, it is easy to stratify. If the SiO2 suspension is added too slowly, the reaction is incomplete, and the content of the SiO2 suspension formed is low and the stability is poor.
[0066] After the reaction is completed, the SiO2 suspension is allowed to stand and age for 4 to 6 days. After aging, large particles are filtered out, and then the aged sol is washed with water to remove impurities, and dried at 100 to 120 degrees to remove moisture, thereby obtaining a stable SiO2 sol, in which the mass percentage of SiO2 is 30 to 50%.
[0067] In the above scheme, in order to make the formed film layer smooth and wrinkle-free, an extrusion wire rod coater is used for coating during the preparation of the first film layer and the second film layer.
[0068] Furthermore, in order to make the double-layer antireflection film formed on the glass surface have both antireflection effect and excellent weather resistance, the present invention preferably has a wet film thickness of 8 to 10 μm for the first film layer and a thickness of 6 to 8 μm for the second film layer after drying.
[0069] Further preferably, in order to ensure good bonding between the various layers described in the present invention, in some embodiments, during the process of preparing the first film layer, after coating the film-forming precursor on the surface of the photovoltaic glass, the film is allowed to stand for more than half an hour to allow the film layer to be deposited more smoothly, thereby ensuring good bonding between the photovoltaic glass and the film layer; similarly, during the process of preparing the second film layer, after coating the film-forming precursor, the film is allowed to stand for more than half an hour to allow the film layer to be deposited more smoothly, thereby ensuring good bonding between the first film layer and the second film layer.
[0070] Some embodiments of the present invention also provide applications of the double-layer anti-reflection film or double-layer anti-reflection film glass described in the aforementioned solution in the fields of optical devices, display technology, photovoltaic industry, building materials, and transportation.
[0071] Some embodiments of the present invention further provide a solar photovoltaic glass, which includes the double-layer anti-reflection film or double-layer anti-reflection film glass described in the above solution.
[0072] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.
[0073] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.
[0074] The testing methods of various performance indicators in the embodiments of the present invention and the comparative examples are as follows:
[0075] Hardness test: According to the standard of "GB / T6739 Determination of pencil hardness of coating", the hardness of the photovoltaic glass after coating is tested to be 3-5H;
[0076] Environmental stability test: The coated glass prepared in the example and the coated glass prepared in the comparative example were placed outdoors for 60 days, and the light transmittance after being placed outdoors for 60 days was tested; then the surface of the coated glass was cleaned with clean water and dried, and then its light transmittance was tested again.
[0077] Moisture-proof performance test: Under room temperature conditions, the coated glass prepared in the embodiment and the coated glass prepared in the comparative example were placed in a shower device simulating rain for 12 hours, then taken out to dry, and the transmittance was tested; then baked at 150°C for 30 minutes, cooled to room temperature, and the transmittance was tested again.
[0078] Example 1
[0079] This embodiment provides a double-layer anti-reflection film, a double-layer anti-reflection film glass, and a preparation method and application thereof, which are as follows:
[0080] 1) Material preparation
[0081] a. Preparation of graphene quantum dots (GQDs):
[0082] Graphene oxide is prepared by immersing graphene in a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid for oxidation treatment, wherein the mass ratio of concentrated sulfuric acid to concentrated nitric acid in the mixed acid solution is 3:1, and the graphene is filtered out after immersion for 0.8 hours.
[0083] Graphene oxide, sodium carbonate, m-phenylenediamine and a second dispersant are mixed in a mass ratio of 1:2:4:100, and placed in a stainless steel autoclave lined with polytetrafluoroethylene, and the raw materials are evenly mixed by ultrasound; further, the mixture is reacted at 200°C for 6 hours. After the reaction is completed, the mixture is cooled, filtered, and purified by semipermeable membrane filtration to obtain the GQDs.
[0084] b. Preparation of TiO2 sol:
[0085] Mixed solution A: Tetrabutyl titanate and anhydrous ethanol are uniformly mixed to form a mixed solution A, in which the mass percentage of tetrabutyl titanate is 40%.
[0086] Dilute acid solution: The dilute acid solution is dilute hydrochloric acid with a hydrogen ion content of 0.01 mol / L.
[0087] Under stirring (stirring speed is 500 rpm), add dilute acid solution to each liter of mixed solution A at a dropping speed of 15 mL / min to adjust the pH of mixed solution A to 2.4. After the addition is completed, continue stirring the reaction for 30 minutes to form a TiO2 suspension.
[0088] After the reaction is completed, the TiO2 suspension is allowed to stand for 5 days to form a stable sol. Finally, the aged sol is washed with pure water to remove impurities and dried at 100°C to obtain a stable TiO2 sol, wherein the mass percentage of TiO2 in the TiO2 sol is 25%.
[0089] c. Preparation method of SiO2 sol:
[0090] Mixed solution E: Tetraethyl orthosilicate and anhydrous ethanol are mixed uniformly at room temperature to form a mixed solution E, wherein the mass percentage of tetraethyl orthosilicate in the mixed solution E is 50%.
[0091] Dilute acid solution: The dilute acid solution is dilute hydrochloric acid with a hydrogen ion content of 0.01 mol / L.
[0092] Under stirring (stirring speed is 500 rpm), add dilute acid solution to each liter of mixed solution E at a dropping speed of 15 mL / min to adjust the pH of the mixed solution E to 2.4. After the addition is completed, continue stirring the reaction for 30 minutes to form a SiO2 suspension.
[0093] After the reaction is completed, the SiO2 suspension is allowed to stand for 5 days to form a stable sol. After aging, large particles are filtered out, and then the aged sol is washed with water to remove impurities, and dried at 105°C to remove moisture to obtain a stable SiO2 sol, in which the mass percentage of SiO2 is 40%.
[0094] 2) Preparation of film precursor:
[0095] Preparation of the first film layer precursor:
[0096] The components are mixed in the following proportions: 12% TiO2 sol, 8% SiO2 sol, 42% deionized water, and 38% anhydrous ethanol; stirred at a speed of 20,000 r / h, and ultrasonic stirring (ultrasonic frequency is 30 KHz) is continued at room temperature for 8 hours to mix the above components evenly, and sealed and aged at room temperature for 24 hours. The formed TiO2 / SiO2 composite sol is the film-forming precursor of the first film layer.
[0097] Preparation of the second film layer precursor:
[0098] The following components were mixed in the following proportions: 60% TiO2 sol; 0.3% GQDs; 39.7% deionized water; stirred at a speed of 20,000 r / h, and ultrasonically stirred (ultrasonic frequency is 30 kHz) for 6 hours at room temperature until the above components were evenly mixed, and sealed and aged at room temperature for 24 hours. The formed TiO2 / GQDs composite sol is the film-forming precursor of the second film layer.
[0099] 3) Preparation of double-layer antireflection film on photovoltaic glass surface
[0100] Photovoltaic glass pretreatment: Rinse the photovoltaic glass to be coated with distilled water, then rinse with ethanol and dry the surface.
[0101] Preparation of the first film layer: The first film layer precursor prepared in this embodiment is coated on the surface of the photovoltaic glass using an extrusion wire rod coater, and the formed wet film thickness is 9 μm; after coating, the photovoltaic glass containing the first film layer is placed at 150°C and baked for 1 hour to solidify the film layer, and then cooled and taken out, and the preparation of the first film layer is completed. After solidification, the thickness of the first film layer is 6.5 μm.
[0102] Preparation of the second film layer: The photovoltaic glass having the first film layer prepared was wiped with 95% ethanol for 5 times to remove dust and impurities, and the surface was dried. The second film layer precursor prepared in this embodiment was coated with an extrusion wire rod coater, and the formed wet film thickness was 9 μm. After coating, the photovoltaic glass was placed under 150°C for baking and drying to solidify the film layer, and then cooled and taken out, and the preparation of the second film layer was completed. After solidification, the thickness of the second film layer was 7.8 μm.
[0103] The photovoltaic glass coated with the double-layer antireflection film prepared in this embodiment was subjected to a hardness test, an environmental stability test and a moisture-proof performance test in sequence. The test results are shown in Table 1.
[0104] Example 2
[0105] This embodiment provides a double-layer anti-reflection film, a double-layer anti-reflection film glass, and a preparation method and application thereof, which are as follows:
[0106] 1) Material preparation
[0107] a. Preparation of graphene quantum dots (GQDs):
[0108] Graphene oxide is prepared by immersing graphene in a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid for oxidation treatment, wherein the mass ratio of concentrated sulfuric acid to concentrated nitric acid in the mixed acid solution is 4:1, and the graphene is filtered out after immersion for 0.8 hours.
[0109] Graphene oxide, sodium carbonate, m-phenylenediamine and a second dispersant are mixed in a mass ratio of 1:1:3:90, and placed in a stainless steel autoclave lined with polytetrafluoroethylene, and the raw materials are evenly mixed by ultrasound; further, the mixture is reacted at 180°C for 8 hours. After the reaction is completed, the mixture is cooled, filtered, and purified by semipermeable membrane filtration to obtain the GQDs.
[0110] b. Preparation of TiO2 sol:
[0111] Mixed solution A: Tetrabutyl titanate and anhydrous ethanol are uniformly mixed to form a mixed solution A, in which the mass percentage of tetrabutyl titanate is 30%.
[0112] Dilute acid solution: The dilute acid solution is dilute hydrochloric acid with a hydrogen ion content of 0.01 mol / L.
[0113] Under stirring (stirring speed is 300 rpm), dilute acid solution is added to each liter of mixed solution A at a dropping speed of 10 mL / min to adjust the pH of mixed solution A to 2.0. After the addition is completed, stirring and reacting is continued for 20 minutes to form a TiO2 suspension.
[0114] After the reaction is completed, the TiO2 suspension is allowed to stand for 4 days to form a stable sol. Finally, the aged sol is washed with pure water to remove impurities and dried at 80°C to obtain a stable TiO2 sol, wherein the mass percentage of TiO2 in the TiO2 sol is 20%.
[0115] c. Preparation method of SiO2 sol:
[0116] Mixed solution E: Tetraethyl orthosilicate and anhydrous ethanol are mixed uniformly at room temperature to form a mixed solution E, wherein the mass percentage of tetraethyl orthosilicate in the mixed solution E is 40%.
[0117] Dilute acid solution: The dilute acid solution is dilute hydrochloric acid with a hydrogen ion content of 0.01 mol / L.
[0118] Under stirring (stirring speed is 500 rpm), add dilute acid solution to each liter of mixed solution E at a dropping speed of 15 mL / min to adjust the pH of the mixed solution E to 2.1. After the addition is completed, continue stirring the reaction for 20 minutes to form a SiO2 suspension.
[0119] After the reaction is completed, the SiO2 suspension is allowed to stand for 4 days to form a stable sol. After aging, large particles are filtered out, and then the aged sol is washed with water to remove impurities, and dried at 100°C to remove moisture to obtain a stable SiO2 sol, in which the mass percentage of SiO2 is 30%.
[0120] 2) Preparation of film precursor:
[0121] Preparation of the first film layer precursor:
[0122] The components are mixed in the following proportions: 11% TiO2 sol, 7% SiO2 sol, 43% deionized water, and 39% anhydrous ethanol; stirred at a speed of 20,000 r / h, and ultrasonic stirring (ultrasonic frequency is 30 KHz) is continued at room temperature for 9 hours to mix the above components evenly, and sealed and aged at room temperature for 12 hours. The formed TiO2 / SiO2 composite sol is the film-forming precursor of the first film layer.
[0123] Preparation of the second film layer precursor:
[0124] The following components were mixed in the following proportions: 57% TiO2 sol; 0.2% GQDs; 42.8% deionized water; stirred at a speed of 20,000 r / h, and ultrasonically stirred (ultrasonic frequency is 30 kHz) for 6 hours at room temperature until the above components were evenly mixed, and sealed and aged at room temperature for 12 hours. The formed TiO2 / GQDs composite sol is the film-forming precursor of the second film layer.
[0125] 3) Preparation of double-layer antireflection film on photovoltaic glass surface
[0126] Photovoltaic glass pretreatment: Rinse the photovoltaic glass to be coated with distilled water, then rinse with ethanol and dry the surface.
[0127] Preparation of the first film layer: The first film layer precursor prepared in this embodiment is coated on the surface of the photovoltaic glass using an extrusion wire rod coater, and the formed wet film thickness is 8.5 μm; after coating, the photovoltaic glass containing the first film layer is placed at 180°C and baked and dried for 0.5 h to solidify the film layer, and then cooled and taken out, and the preparation of the first film layer is completed. After solidification, the thickness of the first film layer is 6 μm.
[0128] Preparation of the second film layer: The photovoltaic glass having the first film layer prepared was wiped with 75% ethanol twice to remove dust and impurities, and the surface was dried. The second film layer precursor prepared in this embodiment was coated with an extrusion wire rod coater, and the formed wet film thickness was 8.5 μm; after coating, the photovoltaic glass was placed under 180°C for baking and drying to solidify the film layer, cooled and taken out, and the preparation of the second film layer was completed. After solidification, the thickness of the second film layer was 7 μm.
[0129] The photovoltaic glass coated with the double-layer antireflection film prepared in this embodiment was subjected to a hardness test, an environmental stability test and a moisture-proof performance test in sequence. The test results are shown in Table 1.
[0130] Example 3
[0131] This embodiment provides a double-layer anti-reflection film, a double-layer anti-reflection film glass, and a preparation method and application thereof, which are as follows:
[0132] 1) Material preparation
[0133] a. Preparation of graphene quantum dots (GQDs):
[0134] Graphene oxide is prepared by immersing graphene in a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid for oxidation treatment, wherein the mass ratio of concentrated sulfuric acid to concentrated nitric acid in the mixed acid solution is 5:1, and the graphene is filtered out after immersion for 0.5 hours.
[0135] Graphene oxide, sodium carbonate, m-phenylenediamine and a second dispersant are mixed in a mass ratio of 1:3:5:110, and placed in a stainless steel autoclave lined with polytetrafluoroethylene, and the raw materials are evenly mixed by ultrasound; further, the mixture is reacted at 220°C for 4 hours. After the reaction is completed, the mixture is cooled, filtered, and purified by semipermeable membrane filtration to obtain the GQDs.
[0136] b. Preparation of TiO2 sol:
[0137] Mixed solution A: Tetrabutyl titanate and anhydrous ethanol are uniformly mixed to form a mixed solution A, in which the mass percentage of tetrabutyl titanate is 50%.
[0138] Dilute acid solution: The dilute acid solution is dilute hydrochloric acid with a hydrogen ion content of 0.001 mol / L.
[0139] Under stirring (stirring speed is 1000 rpm), add dilute acid solution to each liter of mixed solution A at a dropping speed of 20 mL / min to adjust the pH of mixed solution A to 2.8. After the addition is completed, continue stirring the reaction for 40 minutes to form a TiO2 suspension.
[0140] After the reaction is completed, the TiO2 suspension is allowed to stand for 6 days to form a stable sol. Finally, the aged sol is washed with pure water to remove impurities and dried at 100°C to obtain a stable TiO2 sol, wherein the mass percentage of TiO2 in the TiO2 sol is 30%.
[0141] c. Preparation method of SiO2 sol:
[0142] Mixed solution E: Tetraethyl orthosilicate and anhydrous ethanol are mixed uniformly at room temperature to form a mixed solution E, wherein the mass percentage of tetraethyl orthosilicate in the mixed solution E is 60%.
[0143] Dilute acid solution: The dilute acid solution is dilute hydrochloric acid with a hydrogen ion content of 0.001 mol / L.
[0144] Under stirring (stirring speed is 1000 rpm), dilute acid solution was added to each liter of mixed solution E at a dropping speed of 20 mL / min to adjust the pH of the mixed solution E to 2.9. After the addition was completed, the stirring reaction was continued for 40 minutes to form a SiO2 suspension.
[0145] After the reaction is completed, the SiO2 suspension is allowed to stand for 6 days to form a stable sol. After aging, large particles are filtered out, and then the aged sol is washed with water to remove impurities, and dried at 105°C to remove moisture to obtain a stable SiO2 sol, in which the mass percentage of SiO2 is 50%.
[0146] 2) Preparation of film precursor:
[0147] Preparation of the first film layer precursor:
[0148] The components are mixed in the following proportions: 14% TiO2 sol, 9% SiO2 sol, 41% deionized water, and 36% anhydrous ethanol; stirred at a speed of 25000 r / h, and ultrasonic stirring (ultrasonic frequency is 30KHz) is continued at room temperature for 12 hours to mix the above components evenly, and sealed and aged at room temperature for 24 hours. The formed TiO2 / SiO2 composite sol is the film-forming precursor of the first film layer.
[0149] Preparation of the second film layer precursor:
[0150] The following components were mixed in the following proportions: 62% TiO2 sol; 1% GQDs; 37% deionized water; stirred at a speed of 25000 r / h, and ultrasonic stirring (ultrasonic frequency is 40KHz) was continued for 10 hours at room temperature to mix the above components evenly, and sealed and aged at room temperature for 24 hours. The formed TiO2 / GQDs composite sol is the film-forming precursor of the second film layer.
[0151] 3) Preparation of double-layer antireflection film on photovoltaic glass surface
[0152] Photovoltaic glass pretreatment: Rinse the photovoltaic glass to be coated with distilled water, then rinse with ethanol and dry the surface.
[0153] Preparation of the first film layer: The first film layer precursor prepared in this embodiment is coated on the surface of the photovoltaic glass using an extrusion wire rod coater, and the formed wet film thickness is 10 μm; after coating, the photovoltaic glass containing the first film layer is placed at 200°C and baked for 0.5 h to solidify the film layer, and then cooled and taken out, and the preparation of the first film layer is completed. After solidification, the thickness of the first film layer is 6.8 μm.
[0154] Preparation of the second film layer: wipe the surface of the first film layer of the photovoltaic glass that has completed the preparation of the first film layer with 90% ethanol three times to remove dust and impurities, dry the surface, and use an extrusion wire rod coater to form a wet film with a thickness of 10μm for the second film layer precursor prepared in this embodiment; after coating, place the photovoltaic glass at 200°C and bake it for 0.5h to solidify the film layer, cool it and take it out, and the preparation of the second film layer is completed. After solidification, the thickness of the second film layer is 8μm.
[0155] The photovoltaic glass coated with the double-layer antireflection film prepared in this embodiment was subjected to a hardness test, an environmental stability test and a moisture-proof performance test in sequence. The test results are shown in Table 1.
[0156] Example 4
[0157] The preparation process and method of this embodiment are basically the same as those of Embodiment 1, with the difference that, in the process of preparing the double-layer anti-reflection film on the surface of the photovoltaic glass, the thickness of the first film layer precursor and the second film layer precursor coated on the photovoltaic glass are adjusted so that the thickness of the prepared first film layer after curing is 15 μm, and the thickness of the second film layer after curing is 12 μm.
[0158] The photovoltaic glass coated with the double-layer antireflection film prepared in this embodiment was subjected to a hardness test, an environmental stability test and a moisture-proof performance test in sequence. The test results are shown in Table 1.
[0159] Example 5
[0160] The preparation process and method of this embodiment are basically the same as those of Example 1, with the difference being that by adjusting the mass percentage of SiO2 sol SiO2, the mass percentage of TiO2 sol TiO2, and the ratio of each component in the film-forming precursor, the prepared first film layer contains 20% TiO2, 75% SiO2, and 5% other components; the second film layer contains 65% TiO2; 20% GQDs; and 15% other components.
[0161] The photovoltaic glass coated with the double-layer antireflection film prepared in this embodiment was subjected to a hardness test, an environmental stability test and a moisture-proof performance test in sequence. The test results are shown in Table 1.
[0162] Comparative Example 1
[0163] In this comparative example, SiO2 polymer is prepared by a conventional acid-catalyzed sol-gel method, and an organic high molecular polymer is used as a pore-forming agent. The prepared anti-reflection coating liquid is cured and tempered to form a porous silicon dioxide anti-reflection film. The anti-reflection coating layer is made of the anti-reflection coating liquid, as follows:
[0164] 1) Using tetraethyl orthosilicate (TEOS) as a precursor, anhydrous ethanol as a co-solvent, and hydrochloric acid as an acid catalyst, the components are mixed in a ratio of TEOS: anhydrous ethanol: H2O: HCL = 1:20:3:0.08 in molar mass ratio, and stirred at room temperature for 4 hours to prepare an acidic nano-silica sol.
[0165] 2) Using organic high molecular polymer PEG-2000 as a pore-forming agent, the acidic nano-silica sol and PEG2000 were evenly mixed in a mass ratio of 100:2.5, mixed and reacted at a stirring speed of 250 r / min for 1 hour, and aged for 3 days to obtain an anti-reflection coating solution.
[0166] The optical glass was pretreated by the method of Example 1, and then the antireflection coating liquid of this comparative example was coated on one side of the pretreated photovoltaic glass. After the surface was dried, it was baked and solidified to obtain the coated photovoltaic glass.
[0167] The photovoltaic glass coated with the double-layer antireflection film prepared in this comparative example was subjected to a hardness test, an environmental stability test and a moisture-proof performance test in sequence. The test results are shown in Table 1.
[0168] Table 1 Preparation process conditions of each comparative example
[0169]
[0170] It can be seen from the environmental stability test data that the initial light transmittance of the double-layer anti-reflection glass of the embodiment of the present invention is almost the same as that of the anti-reflection glass of comparative example 1, but after 60 days of outdoor testing, the light transmittance of the anti-reflection glass of comparative example 1 decreased by 5.60% compared with that before the test, while the double-layer anti-reflection glass of the embodiment decreased by 2.29% compared with that before the test; after the surface dust was washed with water to remove the influence of the dust, the light transmittance of the anti-reflection glass of comparative example 1 decreased by 0.87% compared with that before the test, while the light transmittance of the double-layer anti-reflection glass of the embodiment of the present invention only decreased by 0.21%, which shows that the environmental stability of the double-layer anti-reflection glass of the embodiment of the present invention is better than that of the anti-reflection glass of comparative example 1.
[0171] It can be seen from the moisture-proof comparison test data that the transmittance of the anti-reflection glass of Comparative Example 1 decreased by 0.68% after 12 hours in a simulated rain shower environment, while the double-layer anti-reflection glass of the embodiment decreased by 0.07% compared with before the test; after baking at 150°C for 30 minutes, the transmittance of the anti-reflection glass of Comparative Example 1 decreased by 0.03% compared with before the test; and after the double-layer anti-reflection glass of the embodiment of the present invention was in a simulated rain shower environment for 12 hours, the transmittance after baking and before the test did not change significantly, which indicates that the anti-reflection glass of Comparative Example 1 is more susceptible to water absorption, and the double-layer anti-reflection film photovoltaic glass of the embodiment of the present invention has better waterproof and moisture-proof performance than the anti-reflection glass of Comparative Example 1.
[0172] It can be seen from the hardness test results that the double-layer antireflection film of the embodiment of the present invention has better hardness than the antireflection film of the comparative example. Therefore, the double-layer antireflection film of the present invention can better enhance the hardness and mechanical strength of the photovoltaic glass.
[0173] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.
[0174] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A double-layer antireflection film, characterized in that: It includes: The first film layer comprises, by mass percentage, 25-65% TiO2, 25-65% SiO2, and 5-15% other components; The second film layer is arranged on the first film layer, and comprises, by weight percentage, 75-94% TiO2, 0.5-8% GQDs, and 5-15% other components.
2. A double-layer anti-reflection film glass, characterized in that: It includes: Glass substrate; The first film layer is disposed on a single side of the glass substrate and comprises, by weight percentage, 25-65% TiO2, 25-65% SiO2, and 5-15% other components; The second film layer is arranged on a single side of the first film layer away from the glass substrate, and comprises, by weight percentage, 75-94% TiO2, 0.5-8% GQDs, and 5-15% other components.
3. The double-layer anti-reflection film glass according to claim 2, characterized in that: The thickness of the first film layer and the second film layer are both 6-8 μm.
4. A method for preparing a double-layer anti-reflection film glass, characterized in that: It includes the following steps: The glass substrate was sequentially washed with water and pre-treated by rinsing with ethanol; The first film layer precursor is coated on one side of the glass substrate, and then dried at a temperature of 150 to 200° C. for 1 to 2 hours to form a first film layer; The first film layer is wiped with anhydrous ethanol, and after the surface is dried, a second film layer precursor is coated on the first film layer, and then dried at a temperature of 150-200° C. for 1-2 hours to form the second film layer.
5. The preparation method according to claim 4, characterized in that: It also includes the following steps: TiO2 sol, SiO2 sol and an organic solvent are mixed to form a first mixed solution, wherein the first mixed solution comprises 11-14% TiO2 sol and 7-9% SiO2 sol by mass percentage; the first mixed solution is subjected to ultrasonic and stirring treatment to be mixed uniformly, and sealed and aged to form a TiO2 / SiO2 composite sol which is the film-forming precursor of the first film layer; TiO2 sol, GQDs and deionized water are mixed to form a second mixed solution, wherein the second mixed solution includes 57-62% TiO2 sol and 0.2-1% GQDs by mass percentage; the second mixed solution is subjected to ultrasonic and stirring treatment to be mixed uniformly, and sealed and aged to form a TiO2 / GQDs composite sol, which is the film-forming precursor of the second film layer; The mass percentage of TiO2 in the TiO2 sol is 20-30%; the mass percentage of SiO2 in the SiO2 sol is 30-50%.
6. The preparation method according to claim 5, characterized in that: The preparation of the GQDs comprises the following steps: The graphene is oxidized by using a mixed acid solution of concentrated sulfuric acid and concentrated nitric acid to obtain graphene oxide; Graphene oxide, sodium carbonate, m-phenylenediamine and anhydrous ethanol are uniformly mixed by ultrasonication in a mass ratio of 1:1-3:3-5:90-110, and reacted at a temperature of 180-220°C for 4-8h; after the reaction is completed, the solid is filtered out and the solid is decontaminated to obtain GQDs.
7. The preparation method according to claim 5, characterized in that: The preparation of the TiO2 sol comprises the following steps: Under stirring conditions, dilute acid solution is added to each liter of a mixture of tetrabutyl titanate and anhydrous ethanol at a rate of 10 to 20 mL / min, the pH of the mixture of tetrabutyl titanate and anhydrous ethanol is adjusted to 2 to 3, the mixture is reacted for 20 to 40 minutes, and then the reaction solution is aged, impurities are removed, and dried to form a TiO2 sol, wherein the mass percentage of tetrabutyl titanate in the mixture of tetrabutyl titanate and anhydrous ethanol is 30 to 50%.
8. The preparation method according to claim 5, characterized in that: The preparation of the SiO2 sol comprises the following steps: Under stirring conditions, dilute acid solution is added to each liter of a mixture of tetraethyl orthosilicate and anhydrous ethanol at a rate of 10 to 20 mL / min, the pH value of the mixture of tetraethyl orthosilicate and anhydrous ethanol is adjusted to 2 to 3, the mixture is reacted for 20 to 40 minutes, and then the reaction solution is aged, impurities are removed, and dried to form a SiO2 sol; the mass percentage of tetraethyl orthosilicate in the mixture of tetraethyl orthosilicate and anhydrous ethanol is 40 to 60%.
9. Application of the double-layer anti-reflection film according to claim 1 or the double-layer anti-reflection film glass according to any one of claims 2 to 3 in the fields of optical devices, display technology, photovoltaic industry, building materials, and transportation vehicles.
10. A solar photovoltaic glass, characterized in that: It comprises the double-layer anti-reflection film according to claim 1 or the double-layer anti-reflection film glass according to any one of claims 2 to 3.